Izloženost starijih osoba nasilju u obitelji - Ajduković, Marina (Array, 2008)
Family violence against elderly persons is one of the complex challenges that modern society is faced with. There has been no systematic research of the family violence against elderly persons in Croatia so far. The aims of this research were: (1) to check the constructive validity of the Survey of the exposure of elderly persons to violence, which survey was designed to research the extent and forms of manifestation of the violence against the elderly in Croatia, and (2) to collect the fi rst data on the violence against the elderly in Croatia. The research was conducted in the area of the City of Zagreb on an appropriate sample of 303 persons (23.4% of men and 76.6% of women) aged between 65 and 97. It has been shown that 61.1% of the respondents have experienced at least one form of family violence during the last year. On average, they mostly experienced psychical violence (24.1%), then material abuse (6.4%), physical abuse (4.4%) and sexual abuse (2.1%). The most frequent perpetrators include husbands (30.15%), sons (16.4%) and daughters (14.01%). The results have been discussed with the view of the future research studies of the violence against the elderly on representative samples in Croatia and the development of social policy of fi ghting violence against elderly citizens